(untitled) (International Journal of Agricultural Research, Innovation and Technology, 2022)
Cassava is one of the most important foods security crops, especially in those regions disposed to difficult crop environments. The crop is also grown in the southern part of Ethiopia and plays an important role for home consumption, animal feed and source of income for small-scale farmers. However, its productivity is still low due to the lack of improved planting materials. Therefore, the experiment was conducted at Jinka Agricultural Research Center’s research site during the 2018 and 2019 consecutive cropping seasons to investigate the adaptability of improved cassava varieties and to select high-yielding variety/varieties for the target area. Four improved cassava varieties (Hawassa-4, Kello, Qulle and Chichu) and one local check were used as treatments and arranged in randomized complete block design with three replications. ANOVA revealed that the interaction between year and variety showed non-significant, whereas varieties performed significantly different (p<0.05) for root yield and other yield-related characters considered in this study. The higher mean value of total root yield was recorded on Hawassa-4 (56.91 ton ha-1) followed by Kello (42.8 ton ha-1) and showed good mean performance for root yield-related parameters than local and Qulle varieties. In general, the varieties Hawassa-4 and Kello yielded better than local checks by 50.95% and 13.5%, respectively. Therefore, the variety Hawassa-4 followed by Kello was identified as the highest yielding and adaptable Cassava varieties at the midland area of South Omo Zone and similar agro-ecologies. Int. J. Agril. Res. Innov. Tech. 12(1): 101-104, June 2022